Optical coherence tomography and coronary angioscopy assessment of healed vulnerable plaque components in patients with coronary artery lesions undergoing elective percutaneous coronary intervention. (25th November 2020) - Kimura, S; Hara, K; Ohmori, M; Tateishi, R; Kaneda, T; Yamakami, Y; Shimada, H; Manno, T; Iishiki, A; Shimizu, M; Fujii, H; Suzuki, M; et al.
Abstract: Background: Many vulnerable plaques would progress without clinical events and might result in healed plaques (HPs). Histopathological or intracoronary image assessment of HPs has been reported. However, the morphological characteristics of HPs remain unclear yet. Purpose: We sought to assess the healed vulnerable plaque components in patients with coronary artery lesions using optical coherence tomography (OCT) and coronary angioscopy (CAS). Methods: We enrolled 47 patients with 50 native coronary artery lesions with angiographical severe stenosis (>90% diameter-stenosis) and without severe calcification (36 lesions with stable angina pectoris (SAP) and 14 acute coronary syndrome (ACS)) undergoing pre-intervention OCT and CAS. HPs was defined as layered phenotype on OCT. Lesion morphologies and plaque characteristics in lesions with HPs were assessed using OCT and CAS images. Results: HPs were observed in 27 lesions (54.0%) and their prevalence were similar among each clinical status (SAP 52.8%, ACS 57.1%, p=1.00). Lesions with HPs had higher prevalence of OCT-macrophage (88.0% vs. 52.0%, p=0.01), CAS-red thrombus (88.8% vs. 52.2%, p=0.004) and CAS-low grade-yellow plaque (grade 1) (55.6% vs. 21.7%, p=0.02) than those without. SAP lesions with HPs had higher prevalence of CAS-yellow plaque (35.3% vs. 5.9%, p=0.09) and OCT-thin-cap fibroatheroma (42.1% vs. 5.9%, p=0.04) than SAP without HPs. ACS lesions with HPs had less CAS-red thrombus (0.0% vs. 50.0%, p=0.03) and OCT-plaque rupture (12.5% vs. 66.7%, p=0.04) than ACS without HPs. Multivariate logistic regression analysis revealed that OCT-macrophages (odds ratio (OR): 6.65, 95%-confidence intervals: 1.07–41.5, p=0.043), CAS-red thrombus (OR 8.77, 95% CI 1.33–57.8, p=0.02), and low grade-yellow plaque (OR 13.05, 95% CI 1.97–86.5, p=0.008) were independently related with the existence of HPs lesions. Combination of these 3 factors showed a high predictive value of OCT-HPs lesions (90.9%). Conclusions: HPs lesions showed the lower lesion vulnerability than common ACS lesions but had more intraplaque inflammatory condition compared with common SAP lesions. Combined CAS and OCT examination might be useful to clarify the plaque components of HPs lesions in vivo, leading to help us understand the clinical significance of HPs. Funding Acknowledgement: Type of funding source: None